2011
DOI: 10.1590/s0103-90162011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Brazilian diamondback moth populations to insecticides

Abstract: Plutella xylostella is a recurring pest on cruciferous crops around the world. In Brazil, it typically requires large number of insecticide sprays, which may lead to fast evolution of resistance. The aim of this study was to assess the susceptibility of Brazilian diamondback moth populations to the insecticides abamectin, deltamethrin, and spinosad. Leaf dip bioassays were used to determine mortality data obtained after 48 h of exposure to insecticides and subjected to Probit analysis. The population from Boni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
1
20
2
5
Order By: Relevance
“…Plutella xylostella is reported to be the first crop pest to have developed resistance against dichlorodiphenyltrichloroethane (DDT) and the first to develop resistance to Bacillus thuringiensis ( Bt ) insecticides [33,37,38] thus, any botanical that is able to offer a significant control will be considered valuable. In Brazil [39], reported that it is normal for farmers to apply between 15-20 insecticide sprays within a cropping season with at least three applications in a week, without success, in an effort to reduce yield losses caused by P. xylostella . The ability of the botanicals to significantly manage the populations of P. xylostella , as well as B. brassicae , in this study is an indication of their potential usefulness in integrated pest management (IPM) of cabbage, especially for resource-limited farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Plutella xylostella is reported to be the first crop pest to have developed resistance against dichlorodiphenyltrichloroethane (DDT) and the first to develop resistance to Bacillus thuringiensis ( Bt ) insecticides [33,37,38] thus, any botanical that is able to offer a significant control will be considered valuable. In Brazil [39], reported that it is normal for farmers to apply between 15-20 insecticide sprays within a cropping season with at least three applications in a week, without success, in an effort to reduce yield losses caused by P. xylostella . The ability of the botanicals to significantly manage the populations of P. xylostella , as well as B. brassicae , in this study is an indication of their potential usefulness in integrated pest management (IPM) of cabbage, especially for resource-limited farmers.…”
Section: Discussionmentioning
confidence: 99%
“…DBM has developed resistance against many different chemical classes of insecticides, such as organophosphates, pyrethroids, benzoylureas, abamectin, indoxacarb and B. thuringiensis ( Bt ) . However, most recently DBM has evolved high levels of resistance against diamide insecticides such as chlorantraniliprole and flubendiamide owing to the extensive use of this new class in different geographies .…”
Section: Discussionmentioning
confidence: 99%
“…The greater effectiveness of spinosad can be explained by its mode of action, targeting different sites such as nicotinic acetylcholine receptor and GABA receptor (Thompson et al, 2000). Our results suggest the absence of cross resistance with pyrethroid and organophosphate as observed by Oliveira et al (2011) for P. xylostella populations, while Sparks et al (1995) showed that spinosad was effective against a Heliothis virescens population resistant to cypermethrin (pyrethroid) and profenofos (organophosphate). Legwaila et al (2014) also demonstrated that spinosad can achieve effective control of resistant P. xylostella population in Botswana.…”
Section: Discussionmentioning
confidence: 48%